DMH1-loaded peptide nanomicelles restore myelin and attenuate neuroinflammation in trigeminal neuralgia via CCL5 suppression - Xia, Shuangyin; Qin, Xiunan; Wang, Yaping (Frontiers in Pharmacology, 2025)
BackgroundTrigeminal neuralgia (TN), a debilitating neuropathic pain disorder, is characterized by demyelination and neuroinflammation, with limited therapies addressing its underlying pathophysiology. Bone Morphogenetic Protein 4 (BMP4) signaling and chemokine CCL5 are implicated in neuroinflammation and oligodendrocyte dysfunction, presenting potential therapeutic targets.MethodsPeptide nanomicelles loaded with the BMP4 inhibitor DMH1 (NM@DMH1) were synthesized and characterized for stability, drug release kinetics, and biocompatibility. In vitro studies assessed oligodendrocyte progenitor cell (OPC) differentiation and anti-inflammatory effects in lipopolysaccharide-induced models. A rat TN model (chronic infraorbital nerve compression) evaluated NM@DMH1’s efficacy in alleviating mechanical allodynia, demyelination, and neuroinflammation. Mechanistic roles of CCL5 were explored using recombinant protein supplementation.ResultsNM@DMH1 exhibited uniform nanostructure (120 nm), high encapsulation efficiency (82%), and pH-responsive sustained release. Treatment enhanced OPC differentiation, reduced pro-inflammatory cytokines (IL-6, TNF-α, IL-1β), and suppressed CCL5 expression in vitro. In TN rats, NM@DMH1 significantly attenuated mechanical pain hypersensitivity (p < 0.01 vs model), restored myelin markers (MBP, MOG), and inhibited neuroinflammatory infiltration. CCL5 supplementation reversed therapeutic benefits, confirming its pivotal role.ConclusionNM@DMH1 represents a nanotechnology-driven strategy targeting TN pathogenesis by promoting remyelination and suppressing CCL5-mediated neuroinflammation. This study advances precision drug delivery for neuropathic pain and highlights CCL5 as a novel therapeutic node, offering translational potential for TN and related neuroinflammatory disorders.